Respons of Early Growth Vetiver (Vetiveria Zizanioides L.) Seedling on Salt Stress Condition - Novita, Aisar (Talenta Publisher, 2020)
Vetiver (Vetiveria zizanioides) is one of the essential oil-producing plants which is commonly called vetiver oil. Agricultural land in Indonesia has a salinity problem estimated at 0.44 million ha, the increase in salinity of agricultural land threatens the stability of agricultural production. This study aims to determine the respons of early growth vetiver (Vetiveria zizanioides L.) seedlings on salt stress condition. This research was conducted in a greenhouse, Faculty of Agriculture, University of North Sumatra, Medan. This study used a non-factorial randomized block design (RBD), namely the salinity (S) which consisted of 3 factors: the EC salinity levels were 0 (distilled water), 4 and 8 ds / m. The salinity stress treatment showed a significant effect of reducing the growth parameters of leaf dry weight, number of stomata and cuticle thickness but did not significantly affect the specific leaf area parameters at 8 WAP. The salinity stress treatment gave significantly better effect in conditions without salinity stress and partly showed better results in the salinity stress condition at the level of 8 dsm-1.